Long‐Term Reoxidation of Hot Briquetted Iron in Various Prepared Climatic Conditions. Issue 1 (17th October 2022) - Daghagheleh, Oday; Schenk, Johannes; Zheng, Heng; Taferner, Bernd; Forstner, Andreas; Rosenfellner, Gerald
Abstract : The application of hot briquetted iron (HBI) in the electric arc furnace (EAF) is a promising method to obtain high‐quality steel products with a guaranteed purity level. However, during the long‐term transportation and storage, the HBI will be partially reoxidized, resulting in a loss of metallization degree. Herein, long‐term reoxidation behaviors of commercial HBI under various prepared climatic conditions are investigated. The results show that HBI exposed to ambient air conditions develops nearly no reoxidation. However, interval and cyclic wetting and drying of HBI lead to the worst metallization loss problem, which must be avoided. Based on morphological analysis, the reoxidation is supposed to occur at the surface and then spread into the center area through cracks or pellet boundaries. The reoxidation gradually decreases the porosity of HBI by the closure of cracks and pores with rust but shows little influence on its physical strength. Abstract : The reoxidation of hot briquetted iron (HBI) is supposed to occur at the surface and then spread into the center area through cracks or pellet boundaries. The reoxidation behaviors depend mainly on the surrounding climatic conditions. The interval wetting and drying of the HBI lead to the largest metallization loss, which shall be avoided.